Mediating Role of Dividend Payout Ratio in the Relationship Between Financial Ratios and Stock Prices among Infrastructure Sector Companies Listed on the Indonesia Stock Exchange - Shinta Dewi; Yulfiswandi (Yayasan Riset dan Pengembangan Intelektual, 2023)
The company's stock price can be impacted by its financial performance, which includes factors such as the Current Ratio, Debt to Equity Ratio, Return on Assets, and Dividend Payout Ratio. The aim of this research was to assess how stock price can be influenced by financial ratio mediated by the Dividend Payout Ratio in infrastructure sector companies listed on the Indonesia Stock Exchange during the period of 2017-2021. The data analysis technique used is panel data regression with Eviews 12 application tools to analyze the influence between variables. This research utilizes secondary data from a sample of 24 infrastructure sector companies that are listed on the Indonesia Stock Exchange (IDX). The findings of this research indicate that the Current Ratio and Debt to Equity Ratio have no significant effect on stock prices, whereas the Return on Assets demonstrates a significant positive effect on stock prices. Although the Dividend Payout Ratio does not act as a mediator between the Current Ratio and Return on Assets on stock prices, it does mediate the effect of Debt to Equity Ratio and stock prices.